Cerebral control of the bladder in normal and urge-incontinent women - Griffiths, Derek (2007)
AIM: To identify age-related changes in the normal brain/bladder control system, and differences between urge incontinence in younger and older women, as shown by brain responses to bladder filling; and to use age, bladder volume, urge incontinence and detrusor overactivity (DO) as probes to reveal control-system function. Functional MRI was used to examine regional brain responses to bladder infusion in 21 females (26 – 85 years): 11 “cases” with urge incontinence and DO (proven previously) and 10 normal “controls”. Responses and their age dependence were determined at small and large bladder volumes, in whole brain and in regions of interest representing right insula and anterior cingulate (ACG). In “controls”, increasing bladder volume/sensation led to increasing insular responses; with increasing age, insular responses became weaker. In younger “cases”, ACG responded abnormally strongly at large bladder volumes/strong sensation. Elderly “cases” showed strong ACG responses even at small bladder volume, but more moderate responses at larger volumes; if DO occurred, pontine micturition center (PMC) activation did not increase. CONCLUSION: Among normal “controls”, increasing age leads to decreased responses in brain regions involved in bladder control, including right insula, consistent with its role in mapping normal bladder sensations. Strong ACG activation occurs in urge-incontinent “cases” and may be a sign of urgency, indicating recruitment of alternative pathways when loss of bladder control is feared. Easier ACG provocation in older “cases” reflects lack of physiological reserve or different etiology. ACG responses seem associated with PMC inhibition: reduced ACG activity accompanies failure of inhibition (DO).